Impact of irritability: a 2‐year observational study of outpatients with bipolar I or schizoaffective disorder. (3rd May 2017) - Berk, Lesley; Hallam, Karen T; Venugopal, Kamalesh; Lewis, Andrew James; Austin, David W; Kulkarni, Jayashri; Dodd, Seetal; de Castella, Anthony; Fitzgerald, Paul B; Berk, Michael
Abstract : Objectives: Many people experience irritability when manic, hypomanic, or depressed, yet its impact on illness severity and quality of life in bipolar and schizoaffective disorders is poorly understood. This study aimed to examine the relationship between irritability and symptom burden, functioning, quality of life, social support, suicidality, and overall illness severity in a naturalistic cohort of people with bipolar I or schizoaffective disorder. Methods: We used data from 239 adult outpatients with bipolar I or schizoaffective disorder in the Bipolar Comprehensive Outcomes Study (BCOS) – a non‐interventional observational study with a 2‐year follow‐up period. Baseline demographic and clinical characteristics of participants with and without irritability were compared. A mixed‐model repeated measures analysis was conducted to examine the longitudinal effect of irritability on clinical and quality‐of‐life variables over follow‐up using significant baseline variables. Results: At baseline, 54% of participants were irritable. Baseline irritability was associated with illness severity, mania, depression, psychotic symptoms, suicidality, poor functioning, and quality of life, but not diagnosis (schizoaffective/bipolar disorder). Participants with irritability were less likely to have a partner and perceived less adequate social support. On average, over follow‐up, those with irritability reported more symptoms, functional impairment, and suicidality. Furthermore, the effects of irritability could not be fully explained by illness severity. Conclusions: Irritability was associated with more negative symptomatic, functional, and quality‐of‐life outcomes and suicidality. The identification, monitoring, and targeted treatment of irritability may be worth considering, to enhance health and wellbeing outcomes for adults with bipolar and schizoaffective disorders.